Pengaruh Pelaksanaan Audit Internal terhadap Pencegahan FRAUD (Kecurangan) (Studi pada PT LEN Industri (Persero) Bandung) - Ardiansyah Dwiky Alfarisy (Universitas Batanghari, 2023)
The purpose of this study was to determine the effect of internal audit on fraud prevention and to determine how much influence internal audit has on fraud prevention. The method used in this research is an empirical study. The population in this study are staff or employees of PT. LEN Industri (Persero) with a total of 25 employees. The sampling technique used was saturated sampling, so that a sample of 25 respondents was obtained. The results of the study show that the tcount value of the implementation of internal audits on fraud prevention is 3.740. By using a significance number or Sig (5%), and N = 14, t = 2.0595 is obtained. The provisions say that if tcount > ttable, then Ha is accepted and Ho is rejected, meaning that the hypothesis that internal audit has an effect on fraud prevention is accepted.